2017
DOI: 10.1096/fasebj.31.1_supplement.970.7
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the metabolic effects of exogenous ketone supplementation – an alternative or adjuvant to the ketogenic diet

Abstract: The ketogenic diet (KD) is a high fat, adequate protein, low carbohydrate diet that has been used clinically to treat refractory pediatric epilepsy for nearly a century. Emerging evidence suggests that the KD is broadly neuroprotective and health‐promoting; therefore, it is now being investigated as a preventative strategy and/or treatment for a wide variety of disorders, including many neurological diseases, cancer, obesity, and diabetes, as well as for enhancing athletic performance and human resilience capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…First, decanoic acid increases the production of ketones (beta-hydroxybutyric acid, acetone, and acetoacetate). Ketones have various anti-inflammatory properties, including the inhibition of the NLRP3 inflammasome [33,34], reduction in the levels of cytosolic pro-inflammatory factors (IL-1β, IL-6, IFN-γ, MCP-1) [35], and inhibition of oxidative stress [36]. Inflammation is known to be integral to the development of CAD, initiating the early stages of atherosclerosis and continuing throughout the process.…”
Section: Discussionmentioning
confidence: 99%
“…First, decanoic acid increases the production of ketones (beta-hydroxybutyric acid, acetone, and acetoacetate). Ketones have various anti-inflammatory properties, including the inhibition of the NLRP3 inflammasome [33,34], reduction in the levels of cytosolic pro-inflammatory factors (IL-1β, IL-6, IFN-γ, MCP-1) [35], and inhibition of oxidative stress [36]. Inflammation is known to be integral to the development of CAD, initiating the early stages of atherosclerosis and continuing throughout the process.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Poff et al showed that the administration of ketone bodies alone was effective in reducing a number of pro-inflammatory cytokines, including IL-1β, IL-6, IFN-γ, MCP-1 and RANTES. This demonstrates that ketone bodies have important anti-inflammatory effects [90]. The publication by Youm et al confirms that BHB has the potential to alleviate inflammatory diseases mediated by the NLRP3 inflammasome.…”
Section: Anti-inflammatory Cardioprotective Potential Of the State Of...mentioning
confidence: 90%